اتجاهات تفسیر النصوص ومدارسه فی الشریعة‌ الیهودیة‌ بحث مستل من أطروحة‌ الدکتوراه فی کلیة‌ العلوم الإسلامیة‌/جامعة‌السلیمانیة‌ دراسة‌ تحلیلة‌ مقارنة‌ - بابکر, محمد أحمد; أمین, سامان وهاب (Sulaimani Journal for Humanities, 2018)
The Torah and Talmud are the two significant sources of law in the religion of Judaism. Therefore, we can clearly notice that during the history of Judaism, the followers of this religion have own view points regarding these two important sources and their roles in the legitimate decisions, attributes and revelation of God. These different viewpoints have caused different sects and school of thoughts and diverse interpretations of the sacred texts of Judaism. It can be seen that some of these lookouts appeared under the rules of supreme empires and nations. Jewish schools in the evolution and permanent change on the Torah and Talmud, and how to interpret and apply in life, due to the environment they lived.